Digital analysis of tooth dimensions and Bolton´s ratios among patients with Class 1 and Class 2 Division 1 Malocclusion - نجا, عبدالرحمن; فادي خليل (Latakia University Journal -Medical Sciences Series, 2023)
Aim: the aim of the study is to assessment of tooth dimensions and Bolton´s ratios in class I and class II division I malocclusion Patients in a Syrian sample by using 3D digital models, (2) to detect any significant differences between the tow groups in tooth widths , anterior and overall Bolton ratios , height of tooth crowns, and (3) to detect any gender differences in these variables. Materials and Methods: Study Design: observational, cross-sectional study for descriptive and analytical purposes at the Orthodontic Dep; University of Tishreen, Lattakia, Syria. Sample Size : A sample of 48 dental casts ( 16 class I malocclusion , 16 class II Div I malocclusion , 16 normal occlusion ), aged between 13 and 25 years,(female-to-male ratio was 1:1 in each group). 3D digital models (Maestro 3D Ortho Studio®) with a dedicated programme were used to measure dental dimensions variables. Results: Significant differences were observed between groups in the mesiodistal widths and height crowns of some teeth .Males had larger teeth than females , no Significant differences for the anterior and overall Bolton ratios of gender , Sexual dimorphism was observed in mesiodistal tooth widths and tooth height. Conclusions: patiens with different types of malocclusion differ in tooth dimensions and gender.